Chitosan hydrochloride/carboxymethyl starch complex nanogels stabilized Pickering emulsions for oral delivery of β-carotene: Protection effect and in vitro digestion study. (15th June 2020) - Li, Xiao-Min; Li, Xuehong; Wu, Zhengzong; Wang, Ying; Cheng, Jie-Shun; Wang, Ting; Zhang, Bao
Graphical abstract: Highlights: Pickering emulsions were found to be stable under thermal treatment. Pickering emulsions protected β-carotene from chemical degradation during storage. Lipid oxidation rate could be delayed by Pickering emulsions. The bioaccessibility of β-carotene in Pickering emulsions was higher than bulk oil. Abstract: β-Carotene was encapsulated in the Pickering emulsions stabilized by chitosan hydrochloride – carboxymethyl starch (CHC-CMS) nanogels. During ultraviolet radiation and storage, the retention of β-carotene in Pickering emulsions was higher than that of other formulations, such as Tween 80 stabilized emulsions (TEs) and bulk oil. The Pickering emulsions were found to be stable during thermal treatment. Meanwhile, lipid oxidation was delayed in Pickering emulsions compared to TEs and bulk oil. The vitro digestion results suggested that the free fatty acids (FFA) released were below 30% for all Pickering emulsions, which indicated that a physical barrier was formed by CHC-CMS nanogels to restrain the lipid hydrolysis. The bioaccessibility of β-carotene in Pickering emulsions was higher than that in bulk oil. This research helped establish a connection between the physicochemical properties of CHC-CMS stabilized Pickering emulsions with their applications in the protection effect and oral delivery of bioactive compounds.